Upaya Penurunan Nyeri Pada Klien Post Hemoroidektomi - Kristanti, Natalia; , Fahrun Nur Rosyid, S.Kep., Ns., M.Kes (2017)
Hemorrhoids are known as hemorrhoids or piles is a disease that is very common in the community and has existed since time immemorial. Currently the act of gold standard healing hemorrhoids is surgical hemorrhoidectomy. However hemorrhoidectomy postoperative pain remains a major problem that is caused by a spasm of perianal. The purpose of author can understand the nursing care of client with post hemorrhoidectomy pain with reporting non-pharmacological measures against of decrease pain. The method used descriptive method with the presentation of case study approach to assessment of nursing care, enforcement of nursing diagnosis, planning, implementation, and evaluation of nursing. The acted of nursing 3x24 hours to client post hemorrhoidectomy taught non-pharmacological techniques to decrease pain that encourage clients to select a comfortable position and gave a flotation cushion when sitting, taught clients relaxation breathing, and taught clients distraction techniques. Acute pain problem is resolved in part, thus requiring further treatment and cooperation with other medical teams, clients and family are indispensable for the success of nursing care.